Religions and Ethno-Religious Differences in Bosnia and Herzegovina. From Laboratories of Hate to Peaceful Reconciliation (Stato, Chiese e pluralismo confessionale, 2016)
The article, peer reviewed, is due to be published in Twenty Years after Dayton. The Constitutional Transition of Bosnia and Herzegovina (Proceedings of the Conference), LUISS University Press, Rome, 2016SUMMARY: 1. Introduction - 2. The Politicization of Religion and the Nationalization of Confessions - 3. The Place of Religion and Religious Confession - 4. The Constituent (Chosen) People and Religious Power-Sharing Mechanism - 5. The Education System and Religious Education - 6. The Legal Status of Churches and the State-Religions Relationship - 7. Conclusion.ABSTRACT: It would be wrong to understand the Bosnian war (the main source of Bosnia and Herzegovina’s current problems) only in terms of a religious war. Yet, it would also be wrong to adopt the explanation that religion had no role in Bosnia and Herzegovina’s catastrophe. The misfortunes that occurred in the region during the first half of 1990s was in many respects the result of the abuse of the people’s religious identity, relieved through myth and tradition that even today remain important inspirations for the future. In this article the Author analyses the genesis of this situation and, in particular, the radical nationalism of Bosnia and Herzegovina, which since the collapse of socialist Yugoslavia has been strictly related to the processes of politicization of religion. Under this perspective, the main aim of the article is to understand the place and the role of religion and confessions in the Country’s current legal system.
Keywords: Diritto ecclesiastico comparato e straniero